Larva de quinto estádio e pupa de Caligo martia (Godart) (Lepidoptera, Nymphalidae, Brassolinae) - Casagrande,Mirna M. (2000)
Description of the fifth larval instar and pupa of Caligo martia (Godart, [1824]) from material reared in southern Brasil are described and illustrated. The larvae feed on two species of Cyperaceae. The Caterpillar and pupa appearences are compared with others Caligo species.